Adsorption of Methylene Blue from Solution Using Anionic Surfactant Modified Palm Seed Powder - Hwaileh, Omar A. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Cationic dyes are widely utilized in plastic, textile, leather and tanning industries. High concentrations of these dyes in aquatic environments pose serious threat to human health and the environment due to their toxic profile. Therefore, various environmental protection agencies and governments have established standard control limits to the quality of domestic and industrial effluents before being discharged to water bodies. Among the various treatment processes, adsorption technique was employed in this study for the treatment of methylene blue (MB) simulated effluents under various operational conditions. Here, palm seed powder (PS) was employed as adsorbent for removal of MB from laboratory simulated colored effluent. The sorption capacity of the PS was improved through surface modification by anionic surfactant (sodium dodecyl sulfate). Comparatively, the modified palm seed powder (MPS) efficiently removed 93% of MB while only 57% removal was recorded by PS after 720 min treatment time. The MPS sorption capacity was affected by the presence of interfering ions (Na+ and Mg2+); however, about 18 mg/g of MB was removed even at salt concentration of 100 mg/L. Freundlich isotherm fits suitably the MPS experimental data more than Langmuir isotherm, indicating multilayer sorption process of MB on the heterogeneous MPS surface. The Weber–Morris models confirmed that intraparticle transport played a significant role in the sorption process. Keywords: Adsorption; modified palm seed powder, cationic dyes removal

ÖZ: Katyonikboyalar genellik’le pilastik, tekstil, deri ve solaryum endüstürilerinde kullanılır. Bu boyaların yüksek konsantreli olanları akuatik çevrelerde, toksik kimliklerine bağlı, isnsan sağlığı ve çevresi için ciddi bir tehdit oluşturmaktadır. Bu yüzden çeşitli çevre koruma kurumları ve devletler, yerel ve endüstriyel akıntıların kalitesi ile ilgili su kaynaklarına dökülmeden önce standart kontrol limitleri belirlemiştir. Çeşitli tehdit süreçlerinin yanısıra, adsorpsiyon (emme) teknikleri, çeşitli mavi metilen tehditleri similasyonunun,türlü kondisyonlar, araştırmasında kullanılmıştır. Burda, palmiye ağacı tohumunun pudrası laboratuvardadaki mavi metileni renk içeren akıntıdan ayırmak icin emici işlemini yapmakta. Palmiye tohumunun soğurma kapasitesi, anyonik yüzeyin(sodyum dodesil sülfat) yüzeysel değişiklikleri ile kanıtlanmıştır. Orantılı olarak, değişmiş olan palmiye tohumu pudrası etkili biçimde mavi metilenin 93% ortadan kaldırmasına karşı, normal palmiye tohumu sadece 57% mavi metileni 720 dakika işlemden sonra yok etmiştir. Modifiye edilmiş palmiye tohumunun soğurma kapasitesi bazı anyonik etkenlerin (Na+ ve Mg2+ ) varlığının tesiri altında değişmiştir. Ancak mavi metilenin yaklaşik 18mg/g, 100mg/L konsantredeki tuzda bile ortadan kaldırılmıştır. Mavi metilenin farklı yapıdaki modifiyeli palmiye tohumu yüzeyinden soğurma sürecindeki değişkenlerinde, Freundlich izotermi, Langmuir izotermine göremodifiye edilmiş palmiye tohumu araştırması verilerine daha uygun. Weber-Morris modelleri kanıtlamıştır ki intraparticle arası ulaşım soğurma sürecinde önemli role sahiptir. Anahtar Kelimeler: Emme; Modifiye edilmis palmiye tohumu pudrası; Katyonik boya çözücü
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Department of Chemistry, 2016. Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Adsorption; modified palm seed powder; cationic dyes removal